Quality of life in people with cognitive impairment: nursing homes versus home care / Azlina Wati Nikmat - Nikmat, Azlina Wati (2014)
The evaluation of quality of life (Qol) among older adults has become increasingly important in health and social science as it provides evidence which may have influential implications for ageing policies. Although this has been studied in developed countries, there are also issues for emerging countries, which have ageing populations. Living arrangements play a pivotal role in determining the Qol of people with cognitive impairment. Although informal care (home-based) is favoured, transition to formal care (residential care) often becomes necessary, especially in the later stages of cognitive impairment. The primary objective of the thesis was to compare the Qol of people with cognitive impairment in the community and nursing homes. In addition, factors that differentiate the Qol of people with cognitive impairment in these two settings were identified. A cross sectional observational study of people with cognitive impairment from government hospitals (home care) and nursing homes was carried out. This study involved interviews with older adults aged between 60 to 89 years old. Participants completed the Qol measurements (the EUROPE Health Interview Survey-Quality of Life and the Assessment of Quality of Life) as well as other measurements that assess factors contributing to Qol (e.g. the Short Mini Mental State Examination, the Barthel Index, the Cornell Scale for Depression in Dementia, the Camberwell Assessment of Needs for Elderly and the Friendship Scale). All measurements were examined for their psychometric properties (reliability, validity and structure). In a pilot study, 49 older adults with cognitive impairment were recruited and completed the questionnaires. Results showed significant differences in Qol and social connectedness among people with cognitive impairment in home care and those in nursing home. No significant differences were found by socio-demographic factors, cognitive severity and depression between the study cohorts. In a primary study, 219 people with cognitive impairment were recruited. The main study finding on the Qol of people with cognitive impairment demonstrated that those receiving home care experienced significantly better Qol. Other findings were that home care recipients had better cognitive function, were less depressed, had fewer unmet needs and reported higher social connectedness compared to nursing home participants. No significant differences were observed with regards to health condition, co morbidities and physical functions between study cohorts.